2014
DOI: 10.1021/jp410305m
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Perturbations to Planar Lipid Bilayer Structures

Abstract: We report on the formation of planar lipid bilayer structures on mica where the bilayer contains the phosphocholine 1,2-dioleoyl-sn-phosphatidylcholine (DOPC), cholesterol, sphingomyelin and sulforhodamine-tagged-1,2-dioleoyl-sn-phosphatidylethanolamine (SR-DOPE). Phase separation is seen for the cholesterol domains within the bilayer structure, and exposure of this supported bilayer to controlled concentrations of ethanol reveals organizational changes on both the micrometer- and molecular-length scales. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 58 publications
(120 reference statements)
3
35
2
Order By: Relevance
“…Recently, Setiawan and Blanchard showed that ethanol interferes with the size and distribution of cholesterol domains in planar lipid bilayer structures [ 37 ]. To determine whether plasma membrane cholesterol could be involved in the inhibitory effect of ethanol, we evaluated the effect of Mβ alone or together with ethanol on FcεRI-mediated degranulation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Setiawan and Blanchard showed that ethanol interferes with the size and distribution of cholesterol domains in planar lipid bilayer structures [ 37 ]. To determine whether plasma membrane cholesterol could be involved in the inhibitory effect of ethanol, we evaluated the effect of Mβ alone or together with ethanol on FcεRI-mediated degranulation.…”
Section: Resultsmentioning
confidence: 99%
“…The instrument used to acquire fluorescence anisotropy decay images has been described previously. [36] Briefly, the instrument is based on an inverted microscope optical configuration (Nikon Eclipse Ti−U). All images were collected using a 10x microscope objective.…”
Section: Methodsmentioning
confidence: 99%
“…DOPC and DOPE are representatives of two bulk lipids found across practically all eukaryotes [43][44][45][46], with PE also being common in prokaryotes [37,47]. The phase behavior of DOPE and DOPC has been investigated in considerable detail [39,40,42,48,49], making deviations from the typical behavior of these systems generally straightforward to identify [29,38,50,51]. Therefore, they are useful for characterizing the behavior of lipids in response to minor additives [29,36,38].…”
Section: Resultsmentioning
confidence: 99%